2019
DOI: 10.1002/maco.201911388
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of open‐cell Ni–Sn–P alloy foams prepared by electroless plating

Abstract: In this study, open-cell Ni-Sn-P alloy foams were prepared by electroless plating. The influence of tin content on the surface morphology and properties of Ni-Sn-P alloy foams were investigated. The surface structure of Ni-Sn-P alloy foams became more uniform and compact with the increase of Sn content.The X-ray diffraction result showed that Ni-Sn-P alloy foams gradually transformed from an amorphous structure into crystallization with the increase of heat-treatment temperature. The introduction of Sn signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…The effect of low tin additives on electroless Ni-P plating is investigated, with improved anticorrosion performance reported in a 3.5 percent NaCl solution [37]. The Ni-Sn-P alloy coating was superior to the Ni-P alloy in terms of surface smoothness and corrosion resistance [38]. Many studies have shown that Ni-Sn-P alloys with a lower amount of Sn applied to them have better anticorrosion properties than Ni-P deposits [32,39].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of low tin additives on electroless Ni-P plating is investigated, with improved anticorrosion performance reported in a 3.5 percent NaCl solution [37]. The Ni-Sn-P alloy coating was superior to the Ni-P alloy in terms of surface smoothness and corrosion resistance [38]. Many studies have shown that Ni-Sn-P alloys with a lower amount of Sn applied to them have better anticorrosion properties than Ni-P deposits [32,39].…”
Section: Introductionmentioning
confidence: 99%